An Exploration of Socio-Economic Problems Faced By Prosthetic Limb Amputees in Multan, Pakistan - Humera Ali, Saima Afzal, (Pakistan Journal of Medical & Health Sciences, 2022)
Amputation is a surgical operation in which a portion of the body is removed such as an arm, foot, leg, hand or finger. Amputation can be performed on any portion of the body, from a tiny area to a big area. Two types of prosthesis limb are used after amputation upper limb prostheses and lower limb prostheses. After amputation, most people use prostheses to carry out their daily activities. This research explains how people use prostheses after amputation and what difficulties people have to go through after using the prostheses. Social, economic and psychological aspects also discussed in this research. The objective of this research is to explore the problems and challenges in income climate and personal characteristics. To find out the health care with prosthetic technology, rehabilitation and satisfaction with prostheses and to investigate the established need and resources for prosthesis limb usage also focused in this research. The universe for the following study was all the prosthetic limb amputees in Multan District. All the prosthetic limb amputees were the population of the study. 15 cases were selected to investigate the study. Non probability purposive sampling technique was used. To measure the socio economic problems faced by prosthetic limb amputees, researcher used the interview guide. As a result questions were asked from the respondents during face to face meeting. In all cases, most of the amputations are due to accidents, diabetes, gunshot and amputation of any part of the body in machinery while working in factories. Most people have lower limb amputation including above or below knee amputation. In mostly cases people of lower limb amputations have severe disability. People with amputation have to go through a lot of troubles and sufferings after having their limbs amputated and having their prostheses implanted. The lives of such people are going through troubles and physical pain. Due to which such people are suffering from a lot of mental stress. The government should provide free prostheses to these disabled people and also help them so that they can meet their needs.